Breaking Barriers: Navigating Mental Health Services for Individuals Facing Homelessness, Addiction, Prison Experiences and Social Exclusion in the Dublin Region - Gallagher, Margaret (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Background: There is an escalating homelessness crisis in Ireland causing growing numbers of people to experience homelessness year on year. People experiencing homelessness (PEH) have higher rates of mental disorder and more complex needs than their housed counterparts. PEH seek mental healthcare across a variety of settings including outpatient, inpatient, emergency care, as well as within the prison system. To date, there has been limited research conducted on this population, and their specific needs. Aim: The aim of this study is to explore the demand for mental health services from people experiencing homelessness in a variety of care settings. Methods: Participants included all persons referred to nine community mental health teams, three inpatient psychiatric units, one emergency department, three specialist community mental health teams for people experiencing homelessness (MHSPEH) and two remand prisons between 1st July 2022 and 30th June 2023. Results Several key aspects of psychiatric service provision for the population were included; population characteristics, psychiatric and medical history, referral outcomes, alternative pathways and complex health needs. PEH exhibit a significant prevalence of mental illness, often accompanied by comorbid vulnerabilities. Overall referrals for psychotic illness were prioritised. A significant proportion of referrals were not accepted because they did not meet the geographical criteria or the threshold for secondary care services. Many of these referrals were made by General Practitioners (GPs), who were then left to manage the ongoing care of patients whose referrals were declined, underscoring an unmet need in the system. In general, referrals were only accepted from other medical professionals with the exception of prison mental health services and specialist mental health services for people experiencing homelessness, where referrals were accepted from non-medical sources. Conclusion This population faces substantial barriers to accessing mental healthcare, exacerbated by resource allocation tied to stringent referral criteria. The high rejection rate for referrals, despite evident clinical need, underscores a critical gap in service provision, leaving GPs to manage complex cases beyond their capacity. While some specialist services, such as those in prisons or for people experiencing homelessness, have adopted more inclusive referral pathways by accepting referrals from non-medical staff, these exceptions highlight the broader systemic shortcomings. Addressing the needs of this vulnerable cohort demands a coordinated, multisystem approach that integrates healthcare, social support, and flexible referral mechanisms, ensuring equitable and effective access to mental health services.
APPROVED